Study of the lightning damage produced in a full-locked wire rope of an aerial cableway. (September 2019) - Fontanari, Vigilio; Menapace, Cinzia; Pedrotti, Ettore
Abstract: The ropes of aerial cableways are directly exposed to atmospheric agents that can detrimentally influence their 'in service' behaviour with dangerous consequences on the whole installation. The lightning strike represents one of the most feared events, since during electric discharge transient a large amount of energy is transferred to the structural parts of the rope in very short time intervals, thus determining a localized thermal shock for the material invested by the electric arc. The local damage effects are clearly identifiable by visual inspection and usually require the substitution of the wire rope. In this paper we investigate the effects of a lightning strike occurred to the carrying rope of a high altitude aerial cableway (Pejo 3000), installed on the Italian side of the Alps. During a periodic visual inspection, an important localized damage in the rope produced by lightning was observed. After an initial attempt to repair it, the rope was dismantled. The damaged section was cut and the wires were subjected to microstructural analysis, static mechanical characterization and finally fractographic observation. The aim was to shed light on the entity of the damage produced by the lightning flashover in order to evaluate the potential danger of this event since, generally, the cableway is not immediately inspected if the atmospheric event does not assume the character of exceptionality. The detailed study of the metallurgical modifications and the measurement of the mechanical deterioration of single wires highlight the microstructural nature of the damage, the strong directionality of the thermal shock effects and the localization of the damage in the external layer of the full locked rope. Highlights: Ropes of aerial cableway undergo frequently to lightning Lightning produces a localized severe damage identifiable by deep craters and wires welding During lightning local melting of metal melting occurs The microstructure in the damaged region is strongly modified The local notches and the microstructural notch sensitivity worse the fatigue behaviours